Phenotypic and genotypic landscape of PROKR2 in neuroendocrine disorders - Martinez-Mayer, Julian; Perez-Millan, Maria Ines (Frontiers in Endocrinology, 2023)
Prokineticin receptor 2 (PROKR2) encodes for a G-protein-coupled receptor that can bind PROK1 and PROK2. Mice lacking Prokr2 have been shown to present abnormal olfactory bulb formation as well as defects in GnRH neuron migration. Patients carrying mutations in PROKR2 typically present hypogonadotropic hypogonadism, anosmia/hyposmia or Kallmann Syndrome. More recently variants in PROKR2 have been linked to several other endocrine disorders. In particular, several patients with pituitary disorders have been reported, ranging from mild phenotypes, such as isolated growth hormone deficiency, to more severe ones, such as septo-optic dysplasia. Here we summarize the changing landscape of PROKR2-related disease, the variants reported to date, and discuss their origin, classification and functional assessment.